Carbon dioxide removal as an integral building block of the European Green Deal - Felix Schenuit; Miranda Böttcher; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2022)
The implementation of the new net emission targets for 2030 and 2050 as part of the European Green Deal is moving the deliberate removal of CO2 from the atmosphere up the agendas of political decision-makers. In its latest report, the Intergovernmental Panel on Climate Change (IPCC) also recently reiterated that net-zero targets cannot be achieved without the deployment of carbon dioxide removal (CDR) methods. The political debate in the European Union (EU) about CDR has changed rapidly in recent years, with almost all political actors now calling for a new regulatory framework for CDR to become an integral building block of EU climate policy. However, fundamental conflicts are brewing over the question as to which removal methods and policy instruments should be implemented and which priorities should be set. There are signs of emerging political alliances on the EU level that will shape the Fit-for-55 legislation in the short term and prestructure the debate on the design of climate policy between 2030 and 2040.
Keywords: 320